Effect of Behavioral Counseling with Shaping Techniques and Assertive Exercises on Student Self Affiliation - Yoga, I Gede Krisna; Gading, Ketut; Dharsana, I Ketut (Department of Guidance and Counseling, FIP, Undiksha, 2017)
The purpose of this study is to determine the effect of Behavioral Counseling With Shaping And Assertive Training Techniques To Self Affiliation and to know the difference of influence between behavioral counseling shaping techniques and assertive training techniques to self-affiliation of students of Class VIII SMP LAB UNDIKSHA.Desain design used is Pretes- Posttest Control GroupDesign. Data analysis method used is t-test. The result of this research is experiment group I shows thitung> t table (5,503> 1,997). Furthermore, treatment techniques of shaping and assertive training techniques show that t count> t table (3.16> 1.99). This proves that, there is a difference between shaping techniques with assertive training techniques against self-affiliation students. From the result of calculation average, obtained 127,57 <119,69, meaning that the mean value of shaping technique count is greater than assertive training technique. For that the third hypothesis that there are differences in the influence of behavioral counseling shaping techniques with assertive training techniques to self-affiliation class VIII students SMP LAB UNDIKSHA.